Philosophy and social change/ edited by Dharmendra Goel - Goel, Dharmendra, (ed.) (New Delhi, 1989)
Any Philosophy has to be a critical assimilation of Man's several worlds. The world of concepts for their own inner coherence and elegance and other, those that have a bearing on more prosaic chores of living, striving regulating society, do naturally attract philosophical reflections. Social change, in a scenario such as India's where juxtaposition of the long tired wom-out old cultures, young renaissance emerging out from the vegeta- tive and pristine ecology, and deeply perennial tra- ditions of oldest collective surge of spirit, pose a trifle confusing even if fascinating prospects for thinkers. In this book Prof. Dharmendra Goel editor of the volumecollected together arguments and reflections of some of the very young philosophers and not so very young philosophers, social scientists, and Administrators to offer a viable analysis of the prob- lem. He expect it to arouse critical response amongst the initiated. The Contributors not shirked strong ideological positions, but the whole quest of all the contribu- tors has been to articulate and reason about an issue rather than to disseminate pre-formed truth. The ideological division among the contributors may sur- face here and there, and thds never allows these dis- cussions to fall flat, but it is hoped that readers would be able to see the Role of Ideas, and Ideology in organising a rationally desirable society, better by reading the points made in different writings and perhaps while assessing the validity of these for- mulations. Are Freedom and Rationality compatible with speedy surge for Economic growth? Some contrib- utors have gone in some depth on this vital ques- tion posed by our contemporary India's Predicament. Did not apathetic stability of the past provided harmony and mutually accommodating tolerance amongst Indians while eruption of ethnic intoler- ance recently could be seen as a direct consequence of the rat-race of cornering Development Advantages among the dispossessed? Can a philosopher of value offer some satisfactory solution for a responsive and efficient model for Social Change? The book will be useful to the scholars &e students in the area of Philosophy, Sociology and Political theory.
Keywords: Social change